Young people and banking products and services in Poland: the results of empirical studies - Buszko, Michał; Krupa, Dorota; Chojnacka, Malwina (Ekonomia i Prawo. Economics and Law, 2019)
Motivation: Banks tend to offer increasingly innovative, distinctive products, to introduce new sales channels, as well as to search for new customers. A special group, more often served by banks, are young people. Aim: The main aim of this study is evaluating the types, preferences and patterns of using banking offers as well as to evaluate major channels of accessing banking products and services by children, youths and young adults. The authors used studies of literature, analysed bank products and services for young people as well as conducted survey research on a group of people under 25 years. Results: Young people represent a primarily multi-product approach and their level of financial knowledge determines the use of modern solutions as well as a high diversity of products. Young people that use banking products and services rarely decide to use offers of other financial institutions.